Dispersing the Light: The Status of Christian Higher Education around the Globe - Glanzer, Perry L. (Christian scholar's review, 2013)
Perry L. Glanzer notes that over the past two decades institutional growth in Christian higher education has slowed to a trickle in the West, but in Eastern Europe, Asia, and Africa it has taken off. The remarkable vigor and growth of Christianity in the global South and East is an obvious driver behind the rise of new Christian universities. Drawing upon a recently compiled database of Christian colleges and universities, this article examines the current state of Christian higher education around the world and evaluates how it is faring in the light of larger trends in Christian and global higher education.